Phosphatidylinositol‐3‐kinase and Akt are required for RIG‐I‐mediated anti‐viral signalling through cross‐talk with IPS‐1. Issue 2 (February 2015) - Yeon, Sang Hyeon; Song, Moon Jung; Kang, Hye‐Ri; Lee, Joo Young
Summary Retinoic acid‐inducible gene I (RIG‐I) is a cytosolic pattern‐recognition receptor that recognizes viruses and triggers anti‐viral immune responses. Activation of intracellular RIG‐I signalling is mediated through interferon‐β (IFN‐β) promoter stimulator‐1 (IPS‐1), an adaptor of RIG‐I, which induces IFN regulatory factor (IRF) 3 activation and type I IFN expression. The phosphatidylinositol‐3‐kinase (PI3K) and Akt pathway is activated in host immune cells upon viral infection. However, the mechanism as to how they work in RIG‐I signalling has not been fully elucidated. Therefore, we investigated the role of PI3K and Akt in the regulation of RIG‐I‐mediated IRF3 activation and type I IFN expression in macrophages. Our results show that Sendai virus infection, which is recognized by RIG‐I, led to IRF3 activation and IFN‐β expression and these responses were attenuated by the PI3K inhibitor (LY294002) and an Akt dominant‐negative mutant in the macrophage cell line(RAW264.7). IRF3 phosphorylation and dimerization as well as IFN‐β expression induced by a synthetic RIG‐I agonist, short poly(I:C), were suppressed by LY294002 or siRNA‐Akt in bone marrow‐derived macrophages. Suppression of PI3K and Akt using a dominant‐negative mutant and siRNA knockdown resulted in attenuation of IRF3 activation and IFN‐β expression induced by RIG‐I itself or its adaptor, IPS‐1. Association of Akt with IPS‐1 increased with short poly(I:C) stimulation and required the pleckstrin homology domain of Akt and caspase‐recruitment domain in IPS‐1. Collectively, our results show that PI3K and Akt are required downstream of IPS‐1 for RIG‐I‐mediated anti‐viral immune responses. The results describe a novel, interactive relationship between RIG‐I downstream signalling molecules resulting in efficient anti‐viral immunity.